The difficulty of locating social disadvantaged situations. Theoretical approach and practical confirmation of the problem in a spanish city - García-Araque, Jesús (Geografares, 2022)
The lack of consensus on how to identify vulnerable spaces is total. From the definitions, to the variables used and the methodology, each author determines those that he considers appropriate. It is hypothesized that there is no infallible method and that all leave some space unnoticed. To demonstrate it, errors in the identification in a Spanish city are revealed, through field work, analysis of the variables used and comparison between previous results, to end up offering a possible solution.